2023
DOI: 10.3390/healthcare11172393
|View full text |Cite
|
Sign up to set email alerts
|

Nurses’ Attitudes and Factors Affecting Use of Electronic Health Record in Saudi Arabia

Awatif M. Alrasheeday,
Bushra Alshammari,
Sameer A. Alkubati
et al.

Abstract: (1) Background: Nurses’ attitudes toward electronic health records (EHRs) is a very valuable issue that needs to be evaluated, understood, and considered one of the main factors that can lead to its improvement or handicap its implementation. This study aimed to assess nurses’ attitudes toward EHRs and associated factors that affect the implementation of EHRs in different hospitals in Saudi Arabia. (2) Methods: A cross-sectional study was utilized to collect data from 297 nurses working in public hospitals and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…A systematic review of 55 articles revealed that there were more facilitators (e.g., productivity/efficiency, quality and data management, surveillance, preventive care) than barriers (e.g., missing data, no standards, productivity loss, overly complex technology) to using EHR to support public health, implying a certain level of use and acceptance of EHR ( Kruse et al, 2018 ). In the US, a descriptive cross-sectional study among nurses from nursing informatics communities (the American Medical Informatics Association and the Healthcare Information and Management System Society) revealed similar findings that nurses used EHR as part of their job several times a day ( Alrasheeday et al, 2023 ; Gartrell et al, 2015 ; Holmes et al, 2021 ).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…A systematic review of 55 articles revealed that there were more facilitators (e.g., productivity/efficiency, quality and data management, surveillance, preventive care) than barriers (e.g., missing data, no standards, productivity loss, overly complex technology) to using EHR to support public health, implying a certain level of use and acceptance of EHR ( Kruse et al, 2018 ). In the US, a descriptive cross-sectional study among nurses from nursing informatics communities (the American Medical Informatics Association and the Healthcare Information and Management System Society) revealed similar findings that nurses used EHR as part of their job several times a day ( Alrasheeday et al, 2023 ; Gartrell et al, 2015 ; Holmes et al, 2021 ).…”
Section: Discussionmentioning
confidence: 94%
“…Furthermore, factors such as healthcare personnel characteristics (e.g., age, gender, leadership role), financial resources, perceived usefulness, and healthcare setting size influence HER deployment ( Alzghaibi & Hutchings, 2022 ). Nurses’ attitudes also impact EHR system utilization ( Alrasheeday et al, 2023 ). A study by Alrasheeday et al (2023) revealed that 81.1% of nurses held a positive attitude toward her use, while 18.9% expressed negativity.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation